Metaphor In English Version Of Sura Ali Imran - Harahap, Ade Nurfitriani (SALTeL Journal (Southeast Asia Language Teaching and Learning), 2019)
This paper intends to analyze one of them Sura in Al-Qur’an. This study was conducted in Sura Ali Imran. The source of the data was taken from the translation of Sura Ali Imran. They were contained in the verses of Sura Ali Imran, and then analyzed the kinds, functions, and the reasons of using metaphor. The kinds are refers to Lakoff and Johnson that divided the metaphor are arranged in order according to which of Halliday’s three metafunctions. Then, the reason is based on Wahab’s four contextual reasons. Based on the data analysis, it was found that there are two kinds of metaphor used in Sura Ali Imran, 5 verses of explicit metaphor and 10 verses of implicit metaphor. The second finding is there are 9 functions used from 13 functions as the breakdown of Halliday’s three metafunction. The next finding found that the reason why the metaphor is used in Sura Ali Imran are because of four contextual reasons. Therefore, it can be concluded that, some messages of the Al-Qur’an in Sura Ali Imran have a stressing point which is delivered in more beautiful words in implicit metaphor that make the readers have a deeply understanding toward the message.